QUANTITATIVE ANALYSIS OF CHORIOCAPILLARIS ALTERATIONS IN SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN DIABETIC PATIENTS. Issue 9 (September 2021) - Loria, Olivier; Kodjikian, Laurent; Denis, Philippe; Vartin, Christine; Dimassi, Sarra; Gervolino, Lucas; Maignan, Antoine; Kermarrec, Ronan; Chambard, Claudine; Pradat, Pierre; Mathis, Thibaud
Abstract : Purpose: To evaluate quantitative alterations of the choriocapillaris in swept-source optical coherence tomography angiography in diabetic patients. Methods: We included normal patients and diabetic patients with and without diabetic retinopathy (DR), excluding patients with macular edema. Angiograms in 3 × 3 mm were acquired with Plexelite 9000 swept-source optical coherence tomography angiography. Choroidal flow voids were analyzed after removal of projection artifacts. The main evaluation was the correlation between choroidal flow voids area (FVA-CC) and DR stage. Results: A total of 120 eyes of 72 patients were analyzed. There were 17 eyes from healthy subjects, 30 eyes without DR, 22 eyes with minimal nonproliferative DR, 30 eyes with moderate nonproliferative DR, 16 eyes with severe nonproliferative DR, and 5 eyes with proliferative DR (PDR). The percentage of FVA-CC for each group was, respectively, 10.9 ± 3.4%, 14.6 ± 4.8%, 17.6 ± 3.5%, 20.7 ± 5.9%, 19.9 ± 2.9%, and 26.6 ± 4.4%. FVA-CC and DR stage significantly correlated ( P < 0.0001). FVA-CC was significantly increased in diabetic patients without DR compared with healthy subjects ( P = 0.008). Conclusion: Diabetes is associated with quantifiable choriocapillaris alterations in swept-source optical coherence tomography angiography. These alterations precede clinical signs of DR and are correlated with DR stage. Abstract : Diabetes mellitus is associated with choriocapillaris alterations that can be quantified in swept-source optical coherence tomography angiography. Macular edema must be excluded for reliable choriocapillaris analysis. Choriocapillaris flow voids significantly correlated with the stage of diabetic retinopathy. They are observed before clinical signs of diabetic retinopathy.